Non-Response to Antibiotic Treatment in Adolescents for Four Common Infections in UK Primary Care 1991-2012: A Retrospective, Longitudinal Study - Ellen Berni; Laura A. Scott; Sara Jenkins-Jones; Hanka De Voogd; Monica S. Rocha; Chris C. Butler; Christopher Ll. Morgan; Craig J. Currie (MDPI AG, 2016)
We studied non-response rates to antibiotics in the under-reported subgroup of adolescents aged 12 to 17 years old, using standardised criteria representing antibiotic treatment failure. Routine, primary care data from the UK Clinical Practice Research Datalink (CPRD) were used. Annual, non-response rates by antibiotics and by indication were determined. We identified 824,651 monotherapies in 415,468 adolescents: 368,900 (45%) episodes for upper respiratory tract infections (URTIs), 89,558 (11%) for lower respiratory tract infections (LRTIs), 286,969 (35%) for skin/soft tissue infections (SSTIs) and 79,224 (10%) for acute otitis media (AOM). The most frequently prescribed antibiotics were amoxicillin (27%), penicillin-V (24%), erythromycin (11%), flucloxacillin (11%) and oxytetracycline (6%). In 1991, the overall non-response rate was 9.3%: 11.9% for LRTIs, 9.5% for URTIs, 7.1% for SSTIs, 9.7% for AOM. In 2012, the overall non-response rate was 9.2%. Highest non-response rates were for AOM in 1991-1999 and for LRTIs in 2000-2012. Physicians generally prescribed antibiotics to adolescents according to recommendations. Evidence of antibiotic non-response was less common among adolescents during this 22-year study period compared with an all-age population, where the overall non-response rate was 12%.